Flume experiments of gravity flows: Transformation from sandy debris flows to turbidity currents with clay matrix separation - Wang, Jiahao; La Croix, Andrew D.; Wang, Hua; Pang, Xiong; Liu, Baojun (Sedimentary geology, 2024)
Sandy debris flows and high-density turbidity currents are two kinds of gravity flows that have been interpreted to produce massive sandstone deposits, yet no consensus has been reached on the depositional mechanism how the deposits should be subdivided. To show differences in the deposits resulting from these two contrastive types of gravity flows, we designed flume experiments (with sand concentrations ranging from 35 wt% to 55 wt%) to examine how gravity flow states and their associated depositional characteristics vary according to their sand:clay ratio and the gradient of slope across which the flows move. The results show that: (1) gravity flows generally occur with two distinct flow layers, consisting of a lower homogeneous mass flow (debris flow) and an overlying upper turbulent cloud (turbidity current). This indicates that flow transformation from a debris flow to a turbidity current is facilitated by low sand content and high slope gradient; (2) the deposited sand bodies contain lower and upper layers which are characterized by inverse and normal grading, respectively, and these are directly related to the bipartite flow state; (3) laminae dip in the direction of flow within the lower sediment layer and are associated with shear forces within the debris flow. We call this laminated structure “laminar sheared layers” and consider this indicative of the laminar flow state that characterizes debris flows; (4) the process of mixing of the flow with ambient fluid causes the clay matrix to separate from the lower debris flow sediments and be subsequently incorporated into the upper turbidity current sediments. This is the cause of the flow transformation. These observations show clearly that sandy debris flows are capable of depositing clean sand bodies. Most significantly, this study demonstrates that the laminar sheared layers are the key sedimentary feature which allows differentiation between sandy debris flow deposits and high-density turbidites, and reveals the occurrence of clay matrix separation, which is important for predicting high-quality oil and gas reservoirs from submarine fan deposits.